Investigating Between Social Intelligence and Moral Intelligence to Academic Achievement in Psychology Students - Dinda Anisa Nuraini; Muhamad Uyun (Psychosophia: Journal of Psychology, Religion, and Humanity, 2023)
In Indonesia, education is regulated within Law Number 20 of 2003 Chapter 6. This proves that education is significant. Education can guide human life, both individual and social life. One of the things discussed in education is academic achievement. Academic achievement is the result achieved by students, there are at least two factors that influence the increase in academic achievement, namely social intelligence and moral intelligence. This study aimed to determine the relationship between social intelligence and moral intelligence with academic achievement in psychology faculty students. The research subjects totaled 110 students using a purposive random sampling technique. Three measuring instruments are used in this study with details of two variables using a scale and one using documentation. The social intelligence variable is measured based on two aspects with eight indicators from Goleman, the moral intelligence variable is measured based on the four aspects from Lennick & Kiel, and then the academic achievement variable uses the student achievement index (IP) in the form of documentation. Analysis was performed using multiple regression. The results of the hypothesis prove that social intelligence and moral intelligence have a significant relationship with academic achievement, with a value of p = 0.006 (p <0.05), r = 0.319, R2 = 0.102, F = 5.370. Thus, it can be concluded that the variables of social intelligence and moral intelligence together make an effective contribution of 10.2% to increasing academic achievement.